Signatures of the Martian regolith components entrained in some impact‐melt glasses in shergottites. (13th August 2018) - Rao, M. N.; Nyquist, L. E.; Ross, D. K.; Sutton, S. R.; Hoppe, P.; Shih, C. Y.; Wentworth, S. J.; Garrison, D. H.
Abstract: Martian regolith components are found in some impact melts (IM) containing Martian atmospheric gases in the shergottites Elephant Moraine (EET) 79001, Tissint, Zagami, and Shergotty. Excess sulfur abundances provide strong indicators for the presence of an exogenous component. High sulfur abundances and the SO3 ‐SiO2 correlation in polished thin section (PTS) EET 79001, 507 (here #507) are comparable to those in Martian soils. Correlations of SO3 with FeO in #507 from Lithology B and of CaO and Al2 O3 in EET 79001, 506 (here #506) from Lithology A suggest the possible occurrence of two varieties of sulfate‐bearing phases in impact‐melt precursors. Fe/S (atomic) ratios of 1.02–1.34 determined in several sulfide blebs in #507 differ from those determined in igneous sulfides (Fe/S = 0.92), and suggest that most sulfide blebs in #507 are not related to igneous sulfides. Fe/S (atomic) ratios in a Tissint glass range from ~0.5 (pyrite) to >1.1 suggesting a mixture of sulfur‐bearing phases. S K‐XANES spectra of the blebs in EET 79001 and Tissint glasses show that sulfur occurs as mixed amorphous sulfide and sulfite. The δ 34 S values and the 87 Sr/ 86 Sr (I) ratios determined in EET 79001 impact melts are consistent with the proposition that the sulfide blebs result from decomposition of secondary sulfates into sulfites during shock heating followed by reduction to sulfides by isentropic cooling. These results suggest the presence in some shergottites of extraneous regolith components containing oxidized S‐bearing species resembling sulfur species present in Martian soils.